Embodied intersubjective engagement in mother–infant tactile communication: a cross-cultural study of Japanese and Scottish mother–infant behaviors during infant pick-up - Negayama, Koichi; Delafield-Butt, Jonathan T.; Momose, Keiko; Ishijima, Konomi; Kawahara, Noriko; Lux, Erin J.; Murphy, Andrew; Kaliarntas, Konstantinos (Frontiers in Psychology, 2015)
This study examines the early development of cultural differences in a simple, embodied and intersubjective engagement between mothers putting down, picking up, and carrying their infants between Japan and Scotland. Eleven Japanese and 10 Scottish mothers with their 6- and then 9-month-old infants participated. Video and motion analyses were employed to measure motor patterns of mothers’ approach to their infants, as well as their infants’ collaborative responses during put-down, pick-up and carry phases. Japanese and Scottish mothers approached their infants with different styles and their infants responded differently to the short duration of separation during the trial. A greeting-like behavior of the arms and hands was prevalent in Scottish mothers’ approach, but not in Japanese mothers’ approach. Japanese mothers typically kneeled before making the final reach to pick up their children, giving a closer, apparently gentler final approach of torso than Scottish mothers who bent at the waist in larger movements of the torso. Measures of the gap closure between the mother’s hand to infant’s head revealed variably longer duration and distance gap closures with greater velocity by Scottish mothers than by Japanese mothers. Further, the sequence of Japanese mothers’ coordinated body actions on approach, contact, pick-up, and hold was more coordinated at six months than at nine months. Scottish mothers were generally more variable on approach. Measures of infant participation and expressivity indicate more active participation in the negotiation during the separation and pick-up phases by Scottish infants. This paper demonstrates a culturally different onset of development of joint attention in pick-up. These differences reflect cultures of every-day interaction.